Modelling the biodiversity enhancement value of seagrass beds. Issue 11 (9th July 2021) - McHenry, Jennifer; Rassweiler, Andrew; Hernan, Gema; Uejio, Christopher K.; Pau, Stephanie; Dubel, Alexandra K.; Lester, Sarah E.
Abstract: Aim: Seagrass beds are declining globally and are increasingly vulnerable to sea level rise (SLR), which could have consequences for the rich biodiversity they support. Spatial variation in the role of seagrass beds in enhancing biodiversity is poorly resolved, limiting our ability to set priorities for conservation and restoration. We aimed to model the biodiversity enhancement value of seagrass beds. Location: Florida Gulf Coast, USA. Methods: We used generalized additive mixed models (GAMMs) to describe the distribution, total cover and species composition of seagrass beds and to estimate their effects on spatial patterns of faunal species richness under three scenarios. Specifically, we: (a) quantified the biodiversity enhancement value of current seagrass beds, (b) inferred the biodiversity value of potential restoration areas and (c) projected potential changes in the distribution and biodiversity enhancement value of seagrass beds due to SLR using low (+0.50 m) and high (+1.0 m) SLR forecasts for 2100. Results: Current seagrass beds supported 43%–64% more species than unvegetated habitats, even when accounting for spatial variability in predicted faunal richness due to other environmental, seascape, temporal and geographic factors. Seagrass restoration in potential habitats would also increase biodiversity in the near‐term (i.e., 43%–45% above unvegetated levels). However, model projections indicate that SLR could result in significant losses of current seagrass beds and potential restoration areas, causing contracted distributions and lower seagrass cover. Overall, these changes could result in significant reductions in the enhancement value provided by seagrasses. Although, there could also be many suitable locations for seagrasses by 2100, with some having either comparable or potentially increased enhancement value. Main conclusions: Our findings highlight the importance of considering spatial variation in biodiversity benefits when planning for seagrass conservation and restoration and when managing the impacts of SLR.